2015
DOI: 10.1111/eva.12288
|View full text |Cite
|
Sign up to set email alerts
|

Using neutral, selected, and hitchhiker loci to assess connectivity of marine populations in the genomic era

Abstract: Estimating the rate of exchange of individuals among populations is a central concern to evolutionary ecology and its applications to conservation and management. For instance, the efficiency of protected areas in sustaining locally endangered populations and ecosystems depends on reserve network connectivity. The population genetics theory offers a powerful framework for estimating dispersal distances and migration rates from molecular data. In the marine realm, however, decades of molecular studies have met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
336
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 244 publications
(347 citation statements)
references
References 156 publications
9
336
2
Order By: Relevance
“…10,000 SNPs derived from ddRAD‐sequencing. As expected (Gagnaire et al., 2015), the RAD‐seq panel showed more power than the microsatellite panel for identifying fine‐grained genetic structure patterns, as well as for detecting outliers. However, overall, both marker panels revealed similar patterns.…”
Section: Resultsmentioning
confidence: 99%
“…10,000 SNPs derived from ddRAD‐sequencing. As expected (Gagnaire et al., 2015), the RAD‐seq panel showed more power than the microsatellite panel for identifying fine‐grained genetic structure patterns, as well as for detecting outliers. However, overall, both marker panels revealed similar patterns.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous analyses of mitochondrial and microsatellite data, which also failed to detect population structure in the Atlantic Ocean (Birt‐Friesen et al., 1992; Tigano et al., 2015). Lack of population structure in marine organisms, including seabirds, is often observed due to apparent lack of barriers to gene flow and/or large population sizes (Friesen, 2015; Gagnaire et al., 2015). In some cases, the use of a high number of markers can increase resolution: In the black‐footed albatross ( Phoebastria nigripes ) for instance, genotyping of thousands of genomewide markers revealed weak but significant population structure among colonies in Japan and Hawaii, where previous results from traditional genetic markers were contradictory (Dierickx, Shultz, Sato, Hiraoka, & Edwards, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlighted the inherent limitations of outlier analyses in detecting signatures of local adaptation in natural populations, especially when the same pattern of differentiation can be driven by multiple factors such as gene flow, genetic drift, recombination rate, and demographic history. Nonetheless, we showed that if we consider the demographic histories and evolutionary scenarios of the focal species, the limitations of the methods to detect outlier loci, and all alternative hypotheses explaining differentiation patterns, outlier analyses could also be used to investigate demographic processes in populations of species that are demographically independent but not yet not genetically differentiated (Gagnaire et al., 2015). Although with five colonies we did not have enough power for more rigorous tests (e.g., genotype–environment association tests), the results from this study are promising in sight of future studies including more colonies from throughout the Atlantic.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been expected that species with a dispersive larval stage should be less differentiated than species with direct development (Hellberg, 1996; Johnson & Seger, 2001; Palumbi & Baker, 1994), and this has been corroborated by meta‐analyzes of the marine population genetics literature (Kelly & Palumbi, 2009; Selkoe & Toonen, 2011). However, planktonic dispersers have also long revealed pronounced genetic breaks between populations of what was recognized as a single species, and these often collocate with well documented biogeographic boundaries (Gagnaire et al., 2015; Pelc, Warner, & Gaines, 2009; Riginos et al., 2011). Marine biogeographic boundaries often coincide with oceanic fronts thought to impose a physical barrier to dispersal and with strong environmental gradients.…”
Section: Introductionmentioning
confidence: 99%